Assessing Factors Contributing to Diarhoea Among Children Under Five Years in Kasese Municipal Council, Kasese District - Stephen, Bagonza (Kabale University, 2023)
Diarrhoea in children remains a major public health problem in Uganda and other countries in the region and is one of the leading contributors to child mortality. of the risk factors for diarrhea in children are preventable. This study was conducted to assess the factors contributing to the spread of diarrhoea among children under 5 years old in Kasese Municipality, Kasese District. Methodology: A descriptive study design was used, employing both quantitative and qualitative approaches, with 375 people as the sample size of mothers of children under five years of age. Results: All 375 study respondents were reached, hence the study achieved a response rate of a. implying that all the women who were presumed to have knowledge about diarrhea among children under 5 years were reached. (75%) of the respondents agreed that lack of knowledge about diarrhea has led to the spread of the disease among children under five years old, while 55.4% of the respondents agreed that the lack of provision of health services in Kasese Municipality has led to the spread of 'Diarrhoea. However, 56.1 % disagreed that too much distance to the health facilities cannot led to the spread of diarrhea among children under five (S) years, but a lack of trained health professionals could, as agreed by 47% of the respondents. This was an indication that the spread of diarrhea is heavily influenced by the healthcare system, which needs to be adequately supported with both qualified and experienced health professionals that can adequately serve. It was found that 81.1 percent of the respondents agreed that failure to wash hands before eating and after visiting the toilet causes diarrhea among children under five years; 68.9 percent agreed that lack of household information on health and sanitation causes diarrhea; and 64.1 percent agreed that failure of the caretakers to wash hands after changing napkins causes diarrhea.